Mental health and quality of life burden in Buruli ulcer disease patients in Ghana - Yaw Ampem Amoako; Nancy Ackam; John-Paul Omuojine; Michael Ntiamoah Oppong; Abena Gyawu Owusu-Ansah; Harriet Boateng; Mohammed Kabiru Abass; George Amofa; Elizabeth Ofori; Portia Boakye Okyere; Michael Frimpong; Freddie Bailey; et al. (BMC, 2021)
Abstract Background Buruli ulcer disease (BUD) is a necrotic skin neglected tropical disease (NTD) that has both a mental and physical health impact on affected individuals. Although there is increasing evidence suggesting a strong association between neglected tropical diseases (NTDs) and mental illness, there is a relative lack of information on BUD's impact on the mental health and quality of life (QoL) of affected individuals in Ghana. This study is to assess the impact of BUD on mental health and quality of life of patients with active and past BUD infection, and their caregivers. Methods We conducted a case control study in 3 BUD endemic districts in Ghana between August and November 2019. Face-to-face structured questionnaire-based interviews were conducted on BUD patients with active and past infection, as well as caregivers of BUD patients using WHO Quality of Life scale, WHO Disability Assessment Schedule, Self-Reporting Questionnaire, Buruli Ulcer Functional Limitation Score and Hospital Anxiety and Depression Scale data tools. Descriptive statistics were used to summarize the characteristics of the study participants. Participant groups were compared using student t test and chi-square (χ 2) or Fisher's exact tests. Mean quality of life scores are reported with their respective 95% confidence intervals. Data was analysed using STATA statistical software. Results Our results show that BUD patients with active and past infection, along with their caregivers, face significant levels of distress and mental health sequelae compared to controls. Depression (P = 0.003) was more common in participants with active (27%) and past BU infection (17%), compared to controls (0%). Anxiety was found in 42% (11/26) and 20% (6/29) of participants with active and past BUD infection compared to 14% (5/36) of controls. Quality of life was also significantly diminished in active BUD infection, compared to controls. In the physical health domain, mean QoL scores were 54 ± 11.1 and 56 ± 11.0 (95% CI: 49.5‒58.5 and 52.2‒59.7) respectively for participants with active infection and controls. Similarly in the psychological domain, scores were lower for active infection than controls [57.1 ± 15.2 (95% CI: 50.9‒63.2) vs 64.7 ± 11.6 (95% CI: 60.8‒68.6)]. Participants with past infection had high QoL scores in both physical [61.3 ± 13.5 (95% CI: 56.1‒66.5)] and psychological health domains [68.4 ± 14.6 (95% CI: 62.7‒74.0)]. Conclusions BUD is associated with significant mental health distress and reduced quality of life in affected persons and their caregivers in Ghana. There is a need for integration of psychosocial interventions in the management of the disease. Graphic abstract